Respuestas
Respuesta dada por:
1
2.
![\frac{ \times + 1}{2x} + \frac{2x + 3}{3x} = \\ mcm = 3x \\ x(x + 1) + 2x + 3 = \\ {x}^{2} + x + 2x + 3 = \\ {x}^{2} + 3x + 3 \frac{ \times + 1}{2x} + \frac{2x + 3}{3x} = \\ mcm = 3x \\ x(x + 1) + 2x + 3 = \\ {x}^{2} + x + 2x + 3 = \\ {x}^{2} + 3x + 3](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Ctimes++%2B+1%7D%7B2x%7D++%2B++%5Cfrac%7B2x+%2B+3%7D%7B3x%7D++%3D++%5C%5C+mcm+%3D+3x+%5C%5C+x%28x+%2B+1%29+%2B+2x+%2B+3+%3D++%5C%5C++%7Bx%7D%5E%7B2%7D++%2B+x+%2B+2x+%2B+3+%3D++%5C%5C++%7Bx%7D%5E%7B2%7D++%2B+3x+%2B+3)
4.
![\frac{2x + 5}{6x} - \frac{x + 6}{4 {x}^{2} } = \\ mcm = 4 {x}^{2} \\ 2x(2x + 5) - (x + 6) = \\ 4 {x}^{2} + 10x - x - 6 = \\ 4 {x}^{2} + 9x - 6 \frac{2x + 5}{6x} - \frac{x + 6}{4 {x}^{2} } = \\ mcm = 4 {x}^{2} \\ 2x(2x + 5) - (x + 6) = \\ 4 {x}^{2} + 10x - x - 6 = \\ 4 {x}^{2} + 9x - 6](https://tex.z-dn.net/?f=+%5Cfrac%7B2x+%2B+5%7D%7B6x%7D++-++%5Cfrac%7Bx+%2B+6%7D%7B4+%7Bx%7D%5E%7B2%7D+%7D++%3D++%5C%5C+mcm+%3D+4+%7Bx%7D%5E%7B2%7D++%5C%5C+2x%282x+%2B+5%29+-+%28x+%2B+6%29++%3D++%5C%5C+4+%7Bx%7D%5E%7B2%7D++%2B+10x+-+x+-+6+%3D+%5C%5C+4+%7Bx%7D%5E%7B2%7D++%2B+9x+-+6)
4.
arvine1:
puedes reportarla... solo para asegurarme quw esta bien
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años